2023
DOI: 10.3389/fpsyg.2023.1131765
|View full text |Cite
|
Sign up to set email alerts
|

The relationships among Taiwanese youth’s polychronicity, multitasking behavior and perceived learning performance in online learning

Abstract: BackgroundThe advancement of digital technology implies the importance of polychronic learning. Since polychronicity is not equivalent to multitasking behavior, they need to be considered separately. However, less research has been explored on how polychronicity is related to multitasking behavior in the educational field.ObjectiveTo explore the relationships among polychronicity, multitasking behavior and learning performance (including knowledge acquisition and learning satisfaction) in an online learning en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Organizational polychronicity is a work requirement to perform multiple tasks simultaneously and switch between them frequently (Asghar et al, 2020;Mattarelli et al, 2015). Existing views have mostly suggested that organizational polychronicity can decrease turnover, and improve individual happiness and job performance (Asghar et al, 2021;Luo et al, 2023;Franczak et al, 2024). However, some findings have confirmed that organizational polychronicity may reduce efficiency, productivity, and task performance (Han and Broniarczyk, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational polychronicity is a work requirement to perform multiple tasks simultaneously and switch between them frequently (Asghar et al, 2020;Mattarelli et al, 2015). Existing views have mostly suggested that organizational polychronicity can decrease turnover, and improve individual happiness and job performance (Asghar et al, 2021;Luo et al, 2023;Franczak et al, 2024). However, some findings have confirmed that organizational polychronicity may reduce efficiency, productivity, and task performance (Han and Broniarczyk, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Existing views have mostly suggested that organizational polychronicity can decrease turnover, and improve individual happiness and job performance (Asghar et al. , 2021; Luo et al. , 2023; Franczak et al.…”
Section: Introductionmentioning
confidence: 99%